Work integrated learning/professional practice in creative arts programs - Wade, B.; Trinidad, Sue; Woodward, A. (TEXT is published by the Australasian Association of Writing Progams, 2012)
This article reports on a project which aimed to re-think, re-leverage and re-imagine the power of industry/education/sector partnerships in the creative arts in Australia. A selection of case studies were collected and analysed to examine the role industry and community engagement plays increative learning and professional practice pedagogy. As one of three key projects exploring pedagogical approaches in the creative arts under the createED umbrella undertaken in 2011, this project also focussed on exploring tertiary-level work integrated learning (WIL) and professional practice in light of the new national creative and performing arts discipline standards. The result was a national benchmarking of best practice; an exploration of the role of the national discipline standards in evaluating the contribution of WIL, and a set of recommendations articulating how to successfully develop effective professional practice and industry partnership within a creative arts curriculum. Our findings were generally consistent with those of the Australian Learning and Teaching Council National Scoping Study: The Work Integrated Learning / WIL Report (Patrick et al. 2008) and extended upon that significant study through our primary focus upon the creative arts.